2019
DOI: 10.3892/etm.2019.7685
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin receptor agonist Piper betle L. ameliorates dexamethasone‑induced early life stress in adult zebrafish

Abstract: Early life exposure to stress has been suggested to be a crucial factor for the development of the brain and its functions. It is well documented that childhood stress is a risk factor for sleep problems in adulthood. Piper betle L. leaf extract (PB) has been used in several traditional medicines to cure various ailments. Recently, PB has been proved to have antidepressant activity. The literature suggests that antidepressants affect the synthesis and release of melatonin through several mechanisms. Thus, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…DEXAtreated adult zebrafish exhibited anxious behavior, lower melatonin, and higher mRNA expression of the nkfb gene compared to the control. Further, results showed increased MT 2 expression during exposure and the suppression of aanat 2; however, no changes in MT 1 and aanat 1 expressions were observed [102]. Hence, exposure to DEXA in the environment may perturb the expression of genes in, e.g., anti-inflammatory, immunity, and molecular aspects in fish.…”
Section: Effects On Fishmentioning
confidence: 91%
See 1 more Smart Citation
“…DEXAtreated adult zebrafish exhibited anxious behavior, lower melatonin, and higher mRNA expression of the nkfb gene compared to the control. Further, results showed increased MT 2 expression during exposure and the suppression of aanat 2; however, no changes in MT 1 and aanat 1 expressions were observed [102]. Hence, exposure to DEXA in the environment may perturb the expression of genes in, e.g., anti-inflammatory, immunity, and molecular aspects in fish.…”
Section: Effects On Fishmentioning
confidence: 91%
“…The anti-inflammatory molecule results demonstrated that the immune gene expression of il-1β, cxcl-8, tnf α, and crp was downregulated following DEXA injection on crucian carp (Carassius auratus) [101]. A study by Kumari et al [102] examined the levels of melatoninrelated genes (MT 1, 2, aanat 1, and aanat 2) and the stress-related (nfkb) gene after exposure of adult zebrafish to DEXA at early life and then treatment with Piper betle L. (PB). DEXAtreated adult zebrafish exhibited anxious behavior, lower melatonin, and higher mRNA expression of the nkfb gene compared to the control.…”
Section: Effects On Fishmentioning
confidence: 99%
“…The results showed improved levels of melatonin‐related behavioural gene expression (MT1, MT2, aanat1 and aanat2) and stress‐related gene expression (NF‐kB) similar to positive control melatonin. 124 …”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Light can be used as a continuous stimulus for 24 hours without a dark phase or with 18 hours of light exposure and 6 hours of flashes of light during the dark phase with 2 x 2 minutes (light x dark) or 4 x 1 minute (light x dark) to disturb the fish's sleep. 17 . The light exposure device consisted of an on and off switch, an adapter, a setting button for dark and light, and a light intensity control button.…”
Section: Research Article Open Accessmentioning
confidence: 99%